Interblock interference (IBI) and time of reference (TOR) computation in OFDM systems. - Celebi, S. (IEEE Transactions on communications)
Orthogonal frequency-division multiplexing (OFDM) is a popular line code scheme that has found application in wideband modem technologies such has asynchronous digital subscriber loop, high bit rate digital subscriber loop, in addition to digital audio broadcast, digital television terrestrial broadcast, and mobile data communication. To prevent interblock interference (IBI), OFDM inserts a guard time sequence, called the cyclic prefix (CP), between each transmitted block. In practice, CP is rarely long enough for the complete elimination of IBI. Understanding the nature of IBI is crucial in subduing its adverse effects. This study characterizes the power spectral density of the IBI in terms of the channel impulse response and the cyclic prefix length. One of the key findings is that the samples of the impulse response tails do not contribute to IBI power uniformly, but rather their contributions grow linearly as the samples move closer to the edges of impulse response. Based on this observation, the study proposes a time of reference computation technique that minimizes the total IBI power as seen by the receiver